On reinstating Heteropogon allionii (Poaceae: Panicoideae) - Drisya, Valiyaparambil; Pradeep, Ayilliath Kuttiyeri (Phytotaxa, 2020)
Heteropogon allionii (Poaceae: Panicoideae) is generally considered as conspecific with H. contortus. Critical studies revealed H. allionii as very distinct taxon which can easily be distinguished from its closely similar taxon, H. contortus by a combination of characters. Hence, H. allionii is reinstated here. A detailed description, illustration and photoplate of both the taxa are provided for easy identification.